The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/s1806-92902015000900003
|View full text |Cite
|
Sign up to set email alerts
|

Growth curve of buffalo grazing on a grass pasture

Abstract: -The objective of this study was to evaluate the performance of 17 buffaloes (Mediterranean), from birth to slaughter age (720 days) with monthly measures of weight, thoracic perimeter, body length, and height at withers. At the end of experimental period, the animals were separated into two different groups for statistical analysis according to slaughter weight: light body weight (LBW, mean 517 kg) and heavy body weight (HBW, mean 568 kg). Buffalo growth occurs in the same way up to weaning age, and after tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Body weight gain of animals after weaning is a substantial feature for growth evaluation which is not only limited within breed, sex, nutrition etc. (Alves and Franzolin, 2015).…”
Section: Average Body Weight Gain Of Buffalo Progeny At Weaning and Ymentioning
confidence: 99%
“…Body weight gain of animals after weaning is a substantial feature for growth evaluation which is not only limited within breed, sex, nutrition etc. (Alves and Franzolin, 2015).…”
Section: Average Body Weight Gain Of Buffalo Progeny At Weaning and Ymentioning
confidence: 99%
“…the measures of bone growth and body length as those are influenced the growth of organs, muscle, and adipose tissue (Alves and Franzolin, 2015). Campêlo et al (2004) reported that the maternal effect is slowly faded away after weaning and the direct genetic effect contributed more in the growth of the animals thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…All dimensional values were converted to grams for mass and to days for time. We supplemented our dataset with other sources in the instances of missing data for domesticated species ( 59 89 ). Given the extensive size variation present in some domesticated species, we made sure to select all variables from the same breed (e.g., German shepherds for dogs) of approximately similar size to wild counterparts under normally reproducing conditions.…”
Section: Methodsmentioning
confidence: 99%